MENINGKATKAN KETERAMPILAN MENULIS NARASI SISWA BERBANTUAN MEDIA GAMBAR SERI DI KELAS VI SD NEGERI 025 TELUK BINJAI KECAMATAN DUMAI TIMUR - Mariati Mariati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is based on the results of writing student narratives that are still low. The purpose of this study was to increase the results of writing narratives of class VI students of 025 State Primary School in Teluk Binjai. This research is classroom action research which consists of two cycles, namely, the cycle I and cycle II. The results showed that in the initial data the class average obtained a value of 63.5, students who completed as many as 13 students with a percentage of 59.09% category incomplete. in the first cycle, the class average obtained a value of 73.6 and students who completed as many as 16 students with a percentage of 72.7% complete category. in the second cycle, the class average obtained a value of 83.73 and students who completed as many as 18 students with a percentage of 81.81% complete category.